Analisis Sediaan Farmasi Di Indonesia Dalam Menunjang Sistem Kesehatan Nasional: A Systematic Review - Hani Putri Febriyanti; Rhaina Al Yasin; Rossa Shafira Nur Sabrina; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pharmaceutical preparations is a term that covers all forms of pharmaceutical preparations ranging from drugs, medicinal ingredients, traditional medicines to cosmetics. This term has been regulated in Government Regulation of the Republic of Indonesia Number 51 of 2009 concerning Pharmaceutical Work. Management of pharmaceutical preparations is a cycle of activities starting from the selection, scheduling needs, receiving, storage, distribution, destruction and withdrawal, control, which is necessary for pharmaceutical service activities. The method used in this study is a Systematic Literature Review (SLR) of ten national journals which were obtained using online database facilities via the Google Scholar, Refseek, and Sciencegate pages. Journals were selected based on publications published between 2018 and 2023. There were obstacles in the implementation of pharmaceutical preparations, including planning that was still conservative, from delays in drug procurement in demand and distribution, resulting in empty drug supplies. However, not all aspects are problematic. There are many other aspects of the mechanism of pharmaceutical preparation that are carefully programmed and procedurally appropriate. This matter needs to be done routinely and continuously, and with written commitments for pharmaceutical preparations in Indonesia in supporting SKN it can be categorized as quite good.